MicroRNA-145 suppresses cell migration and invasion by targeting paxillin in human colorectal cancer cells - Qin, Jun (Int J Clin Exp Pathol, 2015)
A number of cancers show increased expression of paxillin which plays a central role in tumor progression, including colorectal cancer. However, the mechanisms causing paxillin upregulation remains unclear. In our study, bioinformatics analyses suggested that paxillin is predicted to be a direct target of miR-145. We firstly identified paxillin as a new target of miR-145 and demonstrated that miR-145 inhibits paxillin expression by binding to the paxillin mRNA 3’UTR. Therefore, we assume overexpression of paxillin induced by suppression of miR-145 may promote cell migration and invasion. We detected the expression of paxillin and miR-145 in human colorectal cancer tissues by real-time quantitative PCR. Higher expression of paxillin and lower expression of miR-145 was observed in colorectal cancer tissues than corresponding paracancerous tissue. Moreover, the expression of paxillin was negatively correlated with miR-145 expression. A dual-luciferase reporter assay was used to confirm that paxillin was a direct target of miR-145. In CRC cell lines, overexpression of miR-145 could downregulate paxillin protein expression levels, and ectopic overexpression of miR-145 mimics or inhibitor could inhibit or promote cell migration, invasion, proliferation and clone formation in vitro. Taken together, these data suggested that miR-145 plays a pivotal role in colon cancer through inhibiting cell proliferation migration and invasion, and miR-145 may serve as a tumor suppressor by targeting paxillin gene.